2021
DOI: 10.1007/s13300-021-01152-5
|View full text |Cite|
|
Sign up to set email alerts
|

Nationwide Prevalence of Diabetes and Prediabetes and Associated Risk Factors Among Iranian Adults: Analysis of Data from PERSIAN Cohort Study

Abstract: Introduction: Over the past decades prevalence of diabetes has increased in Iran and other countries. This study aimed to update the prevalence of diabetes and prediabetes in Iran and to determine associated sociodemographic risk factors, as well as diabetes awareness and control. Methods: This is a nationally representative cross-sectional survey that included 163,770 Iranian adults aged 35-70 years, from different ethnic backgrounds, between 2014 and 2020. Diabetes was diagnosed at fasting blood sugar Mohamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 42 publications
4
37
1
1
Order By: Relevance
“…Similar to other countries located in the MENA region, Iran has witness an increasing trend in recent years, contributed by different factors including genetics, obesity, physical inactivity, urbanization, and poor nutritional habits [ 22 , 23 ]. In line with the present study, the prevalence of diabetes in most similar national studies was reported to be increasing, ranging from 7.4 to 24.5% [ 24 – 27 ]. These differences in the figures reported for diabetes prevalence can be attributed to differences associated with methods including different age distribution, different sample sizes, different time period, different regional focus, as well as lack of uniform diagnostic criteria.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to other countries located in the MENA region, Iran has witness an increasing trend in recent years, contributed by different factors including genetics, obesity, physical inactivity, urbanization, and poor nutritional habits [ 22 , 23 ]. In line with the present study, the prevalence of diabetes in most similar national studies was reported to be increasing, ranging from 7.4 to 24.5% [ 24 – 27 ]. These differences in the figures reported for diabetes prevalence can be attributed to differences associated with methods including different age distribution, different sample sizes, different time period, different regional focus, as well as lack of uniform diagnostic criteria.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the number of diabetic patients has been rising among the Iranian population for the past 20 years [ 8 ]. A recent study showed a prevalence of 15.0% for diabetes mellitus and 25.4% for prediabetes in some provinces of Iran that did not encompass Tehran [ 9 ]. However, there is a considerable variation in the prevalence of diabetes between different geographical regions of the country [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Updating information on the prevalence, control, treatment, and awareness of diabetes and prediabetes is essential for prioritizing and planning health care services and achieving the goals of the World Health Organization (WHO) Action Plan for the Prevention and Control of NCDs in 2025 13 . In addition, measuring health inequalities is helpful in promoting equality and achieving Sustainable Development Goals (SDGs).…”
Section: Introductionmentioning
confidence: 99%